The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/ntr/ntu200
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Electronic Cigarette Use Among a Population-Based Sample of Adult Smokers: Association With Smoking Cessation and Motivation to Quit

Abstract: Daily use of electronic cigarettes for at least 1 month is strongly associated with quitting smoking at follow-up. Further investigation of the underlying reasons for intensive versus intermittent use will help shed light on the mechanisms underlying the associations between e-cigarette use, motivation to quit, and smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
312
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(337 citation statements)
references
References 23 publications
(19 reference statements)
20
312
3
2
Order By: Relevance
“…Importantly, the quality of the evidence in support of e-cigarettes' effectiveness in helping smokers quit, according to the GRADE system, was again assessed as very low to low (Malas et al, 2016). Considering only studies with a moderate or strong quality score (Malas et al, 2016), 10 studies other than RCTs examined the relationship between e-cigarette use and smoking status in the real world by surveying regular e-cigarette users Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014;Adriaens et al, 2014;Adkison et al, 2013;Christensen et al, 2014;Brown et al, 2014;Biener and Hargraves, 2015). Samples in 5 studies were not representative, and results have to be interpreted with caution Lechner et al, 2015;Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the quality of the evidence in support of e-cigarettes' effectiveness in helping smokers quit, according to the GRADE system, was again assessed as very low to low (Malas et al, 2016). Considering only studies with a moderate or strong quality score (Malas et al, 2016), 10 studies other than RCTs examined the relationship between e-cigarette use and smoking status in the real world by surveying regular e-cigarette users Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014;Adriaens et al, 2014;Adkison et al, 2013;Christensen et al, 2014;Brown et al, 2014;Biener and Hargraves, 2015). Samples in 5 studies were not representative, and results have to be interpreted with caution Lechner et al, 2015;Goniewicz et al, 2013;Dawkins et al, 2013;Polosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another study assessed the effectiveness of e-cigarettes to quit in a representative sample of the English population, and found that e-cigarette users were 60% more likely to report abstinence in comparison to those using no aid or nicotine products over the counter (Brown et al, 2014). The most recent study, a cohort study on a representative sample of adults in 2 US metropolitan areas, found that daily e-cigarette users were 6 times more likely than non-users or triers to report abstinence, whereas non-daily users were 70% less likely to quit compared to non users or triers (Biener and Hargraves, 2015). It is important to highlight that in the sensitivity analysis conducted in one of the two reviews on e-cigarettes' effectiveness, none of differences in study design (longitudinal, cross-sectional) were associated with significantly different results (Kalkhoran and Glantz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to distinguish established users from non-established users because there is a difference in the reason for e-cigarette initiation in addition to the extent of its use [13]. According to previous studies considering current cigarette smokers, the successful smoking cessation rate was higher among daily or intensive e-cigarette users compared with nondaily or intermittent users [14][15][16]. 2 of 8 The general concept of current e-cigarette use is broadly defined to differentiate experimenters from regular users.…”
Section: Introductionmentioning
confidence: 99%
“…Stopping the use of ENDS appears to be due to dissatisfaction with products and/or safety concerns. 5,6 It is important to note that findings of this survey may not be reflective of opinions of ENDS users in India.…”
Section: Is Ends An Effective Tool For Smoking Cessation or Reduction?mentioning
confidence: 93%